2019
DOI: 10.21203/rs.2.11431/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between family history and essential hypertension in Han population in Shanghai China

Abstract: Backgrounds Genetic factor is one of important influencing factors of essential hypertension, and family history (FH) is an important marker of genetic factors.Objective To explore the association between family history and essential hypertension in Han population in Shanghai China.Methods The method of case-control study was used,342 cases of hypertension and 342 controls were selected and investigate their nuclear family members in the both study groups. The diagnostic information of hypertension in all r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
2
0
0
Order By: Relevance
“…This value indicates that family history, stress level, obesity, and consumption of foods that trigger hypertension contribute 38.2% to the incidence of hypertension, while the rest is determined by other variables outside this study. Genetic factors are one of the important factors that influence essential hypertension (Peng et al, 2020). Essential hypertension is a multifactorial disease caused by genetic and environmental factors (Peng et al, 2020 andStaessen et al, 2003), this is consistent with the results of research showing that there are two main factors that influence the incidence of hypertension, namely genetic factors and factors environment (Aune et al, 2016).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This value indicates that family history, stress level, obesity, and consumption of foods that trigger hypertension contribute 38.2% to the incidence of hypertension, while the rest is determined by other variables outside this study. Genetic factors are one of the important factors that influence essential hypertension (Peng et al, 2020). Essential hypertension is a multifactorial disease caused by genetic and environmental factors (Peng et al, 2020 andStaessen et al, 2003), this is consistent with the results of research showing that there are two main factors that influence the incidence of hypertension, namely genetic factors and factors environment (Aune et al, 2016).…”
Section: Discussionsupporting
confidence: 74%
“…Genetic factors are one of the important factors that influence essential hypertension (Peng et al, 2020). Essential hypertension is a multifactorial disease caused by genetic and environmental factors (Peng et al, 2020 andStaessen et al, 2003), this is consistent with the results of research showing that there are two main factors that influence the incidence of hypertension, namely genetic factors and factors environment (Aune et al, 2016). The results showed that the influence of genetic factors on hypertension was around 20-55% (Fang et al, 2019 andLevy et al, 2009).…”
Section: Discussionsupporting
confidence: 74%